(untitled) (Journal of Human Sciences, 2023)
This research paper intends to address an extremely important topic, as it is closely related to the aims of teaching and learning the Arabic language for non-native speakers, which is the subject of tests as a means through which we learn the level of learners in a language skill, the extent of their growth and progress in it, and a way to measure their language proficiency, and a tool To reveal the extent to which goals have been achieved, so the act of constructing and designing tests - whether oral or written-is a very complex act that requires careful and sufficient knowledge of a range of linguistic and psychological elements and foundations. Therefore, this study aimed to determine the linguistic and psychological bases upon which to build language proficiency tests and to indicate the extent to which proficiency tests in the Arabic language are fulfilled for non-Arabic speakers by these standards and problems facing Arabic language teachers of non-native speakers in building and using these tests. Ibn Qutbah took the concept of the multiplicity of worlds, a procedural approach, in the semantic analysis of the Prophet’s hadith, and access to the significance of his speech. Therefore, in this paper, we will seek to demonstrate Ibn Qutayba’s approach to the concept of the multiplicity of worlds (possible worlds) within the interpretation of the problem from the hadith of the Prophet, by means of a descriptive and analytical approach to explain and analyze the phenomenon.